Mosmo Is Required for Zebrafish Craniofacial Formation - Camacho-Macorra, Carlos; Sintes, Marcos; Tabanera, Noemí; Grasa, Irene; Bovolenta, Paola; Cardozo, Marcos J. (Frontiers in Cell and Developmental Biology, 2021)
Hedgehog (Hh) signaling is a highly regulated molecular pathway implicated in many developmental and homeostatic events. Mutations in genes encoding primary components or regulators of the pathway cause an array of congenital malformations or postnatal pathologies, the extent of which is not yet fully defined. Mosmo (Modulator of Smoothened) is a modulator of the Hh pathway, which encodes a membrane tetraspan protein. Studies in cell lines have shown that Mosmo promotes the internalization and degradation of the Hh signaling transducer Smoothened (Smo), thereby down-modulating pathway activation. Whether this modulation is essential for vertebrate embryonic development remains poorly explored. Here, we have addressed this question and show that in zebrafish embryos, the two mosmo paralogs, mosmoa and mosmob, are expressed in the head mesenchyme and along the entire ventral neural tube. At the cellular level, Mosmoa localizes at the plasma membrane, cytoplasmic vesicles and primary cilium in both zebrafish and chick embryos. CRISPR/Cas9 mediated inactivation of both mosmoa and mosmob in zebrafish causes frontonasal hypoplasia and craniofacial skeleton defects, which become evident in the adult fish. We thus suggest that MOSMO is a candidate to explain uncharacterized forms of human congenital craniofacial malformations, such as those present in the 16p12.1 chromosomal deletion syndrome encompassing the MOSMO locus.